2021
DOI: 10.19045/bspab.2021.100128
|View full text |Cite
|
Sign up to set email alerts
|

A review on recent advances in chitosan applications

Abstract: Chitosan, derivative of chitin is the second most abundant natural polymer and is widely distributed throughout the nature. The numbers of applications of chitosan and their derivatives have been increasing steadily in the last decade. Chitosan has been shown to be a versatile nontoxic material with multiple responses. To date, there is enough evidence indicating that after chitosan application plants can acquire enhanced tolerance to a wide variety of pathogenic microorganisms. A high antimicrobial activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Further, from the results of the study it can be suggested that the inhibitory effect of chitosan is dose-dependent and it increases with increasing the concentration of chitosan. These results are similar to the findings of Lin et al (2020), andBibi et al (2021). Further, both methods viz., agar dilution and well diffusion revealed a significant inhibition zone at the concentration of 15 mg/µl and this inhibition zone is greater than the inhibition zone observed at the remaining two concentrations (P ≤ 0.05).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Further, from the results of the study it can be suggested that the inhibitory effect of chitosan is dose-dependent and it increases with increasing the concentration of chitosan. These results are similar to the findings of Lin et al (2020), andBibi et al (2021). Further, both methods viz., agar dilution and well diffusion revealed a significant inhibition zone at the concentration of 15 mg/µl and this inhibition zone is greater than the inhibition zone observed at the remaining two concentrations (P ≤ 0.05).…”
Section: Discussionsupporting
confidence: 90%
“…The interaction of chitosan with different types of fungi depends on the composition of the cell wall, and when the reaction occurs, the polymer interferes with the growth of the fungus. Further, some previous research also suggested that chitosan molecules may diffuse within the hyphae and may interfere with enzymes involved in the growth of fungi (Kong et al, 2010;Zhang et al, 2015;Bibi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chitin is an organic mucopolysaccharide found in crustaceans, insects, and similar organisms, is widely recognized as comprising 2-acetamido-2deoxy-β-D-glucose units linked via β (1→4) connections. The chitosan is the substance (1, 4linked 2-amino-2-deoxy-β-D-glucan), a derivative of chitin that is formed when chitin's deacetylation reaches approximately 50 per cent [5].…”
Section: Structure and Source Of Chitosanmentioning
confidence: 99%